Three strategies to improve your collaborative efforts - Weaver, Liz (The Latest, 2021)
Collaboration can be challenging work. We convene colleagues together and try to work collaboratively, often providing only limited support and resources to move the collective effort forward. It is no wonder that the experience of collaboration can be frustrating.
Keywords: Libre accès; OBNL

Solving the Puzzle of Collaborative Governance - Weaver, Liz (Tamarack Institute, 2021)
There is a substantive amount of literature about collaboration and collaborative work but relatively little that identifies the nuts and bolts of collaborative governance including process, structure, accountability, engagement, and effectiveness. This article is for changemakers encountering challenges with collaborative governance within their work.
Keywords: Canada; Libre accès

Three strategies to improve your collaborative efforts - Weaver, Liz (The Latest, 2021)
Collaboration can be challenging work. We convene colleagues together and try to work collaboratively, often providing only limited support and resources to move the collective effort forward. It is no wonder that the experience of collaboration can be frustrating.
Keywords: Libre accès; OBNL

Solving the Puzzle of Collaborative Governance - Weaver, Liz (Tamarack Institute, 2021)
There is a substantive amount of literature about collaboration and collaborative work but relatively little that identifies the nuts and bolts of collaborative governance including process, structure, accountability, engagement, and effectiveness. This article is for changemakers encountering challenges with collaborative governance within their work.
Keywords: Canada; Libre accès